INDIVIDUALIZED INTERVENTION PROGRAM FOR LEARNING DISABILITIES AND ADHD - MARIA ANCA; DORINA TALAŞ (Studia Universitatis Babes-Bolyai, 2012)
ABSTRACT. As pedagogical approach presented focused on the intervention for remedial purpose for a student with learning disabilities and ADHD, the integrated conceptual model, the main basis of this study has used many aspects of executive functions with special features in the field of ADHD but in the same time played an important role in solving Romanian language tasks and mathematics tasks.